آليات إعادة التوازن العقدي في التشريع الجزائري - بن عمر فاتن; طلحي أسماء (جامعة المسيلة, 2025)
A contract is considered an agreement between two or more wills to produce a specific legal effect; in principle, it is derived from the doctrine of the autonomy of will. However, contractual balance may be disrupted due to an imbalance in the performances of the parties, which may result in one party being disadvantaged and weakening their contractual position. Therefore, the Algerian legislator intervened to address this imbalance and protect the weaker party by enacting special laws such as the Consumer Protection Law, which aims to combat abusive clauses in adhesion contracts and ensure the weaker party’s right to effective legal protection. In addition, the law grants judge's broad discretionary powers allowing them to amend or annul the contract in cases of proven exploitation or disadvantage, or when unforeseen circumstances alter the nature of the contractual obligations—a concept known as the theory of unforeseen circumstances. This intervention represents a limited modification of the principle that "the contract is the law of the parties," but it is necessary to ensure balance and fairness in contractual relationships, especially in contracts where one party holds significantly more power than the other.